Training on Processing Household Waste into Organic Liquid Fertilizer for PKK Cadres in Baturetno Village - Ane Permatasari; Triyono Triyono; Bhakti Gusti Walinegoro (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
Plant fertilizers can be made from household waste from living things such as leftover vegetables, fish bones, side dishes, or herbs that are no longer edible. These materials can be recycled into liquid organic fertilizer. The purpose of the community service held in Baturetno, Bantul, was to increase the understanding of Women's Empowerment Cadres about household waste management and qualify them to process household waste into organic liquid fertilizer. The problems in Baturetno Village were an excessive daily household waste, a lack of public awareness of the dangers of waste problems, and a lack of household waste processing activities. To overcome this problem, the efforts made include socializing the harm of waste problems for life, providing training on how to process household waste into organic liquid fertilizer, and distributing composter containers. This program has increased cadre awareness of the importance of processing household waste to maintain a clean environment, avoid disease spread due to rotten garbage, and increase the fertility of plants in the fields.